Stimulating innovations for sustainable agricultural practices among smallholder farmers: persistence of intervention matters - Bedi, S.M.; Kornher, L.; Braun, J. von; Kotu, Bekele Hundie (Informa UK Limited, 2022)
As part of the dissemination of sustainable intensification (SI) of agricultural practices in northern Ghana, farmers were conditionally induced with inputs to adopt the SI practices. We study the effects of the conditional inducement on maize yield and net income of farmers under a quasi-randomised phase-out design. We examine the effects of the inducement by comparing continuous induced farmers with past induced and non-induced farmers. Our results indicate that the conditional inducement led to an increase in the maize yield and the net income of continuously induced farmers, on average. Estimates also suggest that the continuously induced farmers would have had their maize yields and net incomes decreased by about 64 per cent and 54 per cent, respectively if the inducement had been discontinued. Distributional analysis reveals that the inducement effects are heterogeneous and that past inducement impacted more on the maize yield and the net income of farmers at the lower quantiles. We conclude that appropriate conditional inducement can stimulate farmers’ adoption. Besides, the duration of intervention matters and must not be overlooked in interventions that necessitate gaining experience and learning.